2002
DOI: 10.1034/j.1600-0609.2002.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular T cell cytokines in patients with B cell chronic lymphocytic leukaemia (B‐CLL)

Abstract: Analysis of cytokine production is a tool to functionally characterise T cells. In this study, spontaneous and polyclonal activation induced cytokine production in T cells were assessed by flow cytometry in patients with B-CLL. Patients with progressive disease had a significantly increased number of T cells spontaneously producing IL-2, IL-4 and GM-CSF as compared to healthy donors and patients with non-progressive CLL, which was not the case for TNF-alpha and IFN-gamma producing T cells. However, no differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 37 publications
2
53
0
Order By: Relevance
“…The criteria for diagnosis and disease progression have been previously described. 5 Direct surface and intracellular immunofluorescence staining were performed for the evaluation of the expressions of all studied proteins and the distribution of cell cycle phases. Cells were then analyzed by flow cytometry using a FACScalibur.…”
Section: To the Editormentioning
confidence: 99%
“…The criteria for diagnosis and disease progression have been previously described. 5 Direct surface and intracellular immunofluorescence staining were performed for the evaluation of the expressions of all studied proteins and the distribution of cell cycle phases. Cells were then analyzed by flow cytometry using a FACScalibur.…”
Section: To the Editormentioning
confidence: 99%
“…21 IL-4-expressing T cells are expanded in CLL patients, and a higher proportion of IL-4-expressing T cells is evident in patients with aggressive disease. 22 In proliferation centers, CLL cells are in intimate contact with T cells that express abundant IL-4. 23,24 In vitro, IL-4 promotes CLL cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the stimulation protocol employed in this study was not sensitive enough to detect IL-4 and IL-5 [39]; as PMA/ionomycin stimulation of IL-4 and IL-10 was insufficient for their intracellular detection, often requiring secondary culture with cytokines followed by re-stimulation with mitogen [40]. However, some studies have shown an induction of intracellular IL-4 with only primary stimulation with PMA/ionomycin [38]. Stimulation of cell cultures with human HSP60 [38,41] resulted in a statistically significant increase in mean fluorescence intensity for intracellular TNF-α in the CP and CHD patients compared with gingivitis group (Table 2, Figure 2), but no significant differences were seen amongst the 4 groups for intracellular IFN-γ, IL-2, IL-4 IL-5 and IL-17.…”
Section: Discussionmentioning
confidence: 90%
“…This is not surprising as unstimulated cells usually produce little or no measurable cytokines [37] except in patients with progressive malignancies [38]. PMA/ionomycin stimulation of cells resulted in an increase in the mean fluorescence intensity of TH1 cytokines in both controls and patients with CP and CHD ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation